Optimizing the Role of the Health Service in Handling and Preventing Stunting in Merauke Regency, South Papua - Rachmat Agung; Ilham Majid (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This research has a phenomenon, namely that in Merauke Regency there are still problems with stunting, the lack of a fixed place to carry out posyandu activities and the lack of understanding of parents regarding child rearing patterns. The aim of this research is to determine the Optimization of the Role of the Health Service in handling Stunting in Merauke Regency and to determine the obstacles in the Role of the Health Service in Handling Stunting in Merauke Regency. The theory used, according to Jim Ife (in Pawalin, 2017), has several indicators, namely Facilitative Role, Educational Role, Representational Role and Technical Role. The research method used by the author in this research is the Qualitative Method, this method is related to opinions, thoughts, ideas or confidence in the objects to be researched, all the required data is presented in the form of words and language. The results of the research show that handling of stunting in Merauke Regency includes several programs, namely Posyandu, Pregnant Women's Class, PTTD, and PMT, there is socialization in the form of counseling carried out at meetings such as posyandu and mothers' groups with the assistance of the Community Health Center and cadres. village cadres. This is done with the hope that the public will be aware of the importance of health regarding Stunting Management so that they are free from stunting in the future. Several factors that become obstacles in handling stunting are the lack of understanding of parents regarding parenting patterns, eating patterns, a clean environment and the lack of a fixed place to carry out posyandu activities.